Youth sports in the wake of COVID-19: a call for change - Watson, A.; Scott Koontz, J. (British Journal of Sports Medicine, 2021)
The COVID-19 pandemic has had a significant impact on virtually every facet of life throughout the world. Among youth athletes, the cancellation of school and sports was accompanied by decreases in physical activity and significant mental health consequences. The reintroduction of sports has varied considerably, with the full return of sports in some regions and continued restriction in others. Given that youth sports faced serious problems prior to the pandemic including high costs, professionalisation, decreased participation and barriers to access,1 we should consider more than just returning to `normal`. This unexpected pause provides an opportunity to not only guide the return to youth sport participation but invest in programmes and organisations that increase physical activity and increase access to sports for all children.